The Recitation Method Development in Online Learning for Reading Comprehension Students in the English Literature Study Program - Juli Rachmadani Hasibuan; Feriyanti Elina Gultom; Christine Helena Natalia (RIRAI Publisher, 2022)
In Universitas Negeri Medan, there are 6 assignments for each subjects to be accomplished in each semester, namely Routine Tasks, Critical Book Reviews, Critical Journal Reviews, Mini Research, Engineering Ideas and Projects. In doing all these tasks, of course, reading has important role. A good reading gives accurate data and information in accomplishing all tasks. To avoid a very boring reading and provide challenges, develop a good learning methods is a must. The aims of the study is to investigate how the recitation learning methods developed for the reading comprehension of the students. The data obtained through the observation, questionnaires, and interviews to know the competence of students in reading comprehension. Adopting research development method that refers to the development of model, this development research data is qualitative and quantitative data. The objective of this research is to develop recitation methods in online learning for reading comprehension skills of the students of English Literature Study Program in Universitas Negeri Medan. The results of this study are expected to be able to give contribution to the students who take Reading Subject and also to the lecturers who teach Reading Subject to be more efficient and effective in using appropriate learning methods in Reading Subject.